2020
DOI: 10.1177/0003319720969997
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Indices in Patients With Acute Ischemic Stroke Treated With Intravenous Tissue Plasminogen Activator: Clinical Yield and Utility

Abstract: Inflammation indices derived from complete blood counts (CBCs) have been proposed to estimate benefit and risk of intravenous (IV) tissue plasminogen activator (tPA) in acute ischemic stroke. In 165 acute ischemic patients, the neutrophil-to-lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio, and systemic immune-inflammation index (SII) were calculated before and 24 hours after IV tPA. The area under receiver operating characteristic (AUC-ROC) curves, and positive and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…A meta-analysis could not be performed. However, a systematic review indicated that a higher admission PLR could be associated with radiological bleeding, with both Ferro et al 23 and Topcuoglu et al 18 reporting this. Ferro et al‘s results, split into grades of radiological bleeding, while significant in univariate analyses, did not provide a significant result in multivariate modelling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis could not be performed. However, a systematic review indicated that a higher admission PLR could be associated with radiological bleeding, with both Ferro et al 23 and Topcuoglu et al 18 reporting this. Ferro et al‘s results, split into grades of radiological bleeding, while significant in univariate analyses, did not provide a significant result in multivariate modelling.…”
Section: Resultsmentioning
confidence: 99%
“…A lower delayed PLR was observed in patients with ENI in both studies included in the systematic review, but this reached statistical significance only in the results of Topcuoglu et al and not Inanc & Inanc. 18 , 21…”
Section: Resultsmentioning
confidence: 99%
“…In another study, SII was associated with 90-day functional outcome [ 62 ]. In patients submitted to IVT, an increased 24-h SII was associated with poor functional outcome [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the SII index, ROC-AUC was 0.802, sensitivity was 58.7%, and specificity was 72.7%. As a result, it was concluded that the SII index and NLR provided moderate benefit in predicting the risk of bleeding that might occur following thrombolytic therapy (24). Similarly, it was emphasized that the SII index was a marker that predicted hemorrhagic transformation in patients who had a stroke due to large artery atherosclerosis of anterior circulation (25).…”
Section: Discussionmentioning
confidence: 99%